2021
DOI: 10.1107/s2053229621009293
|View full text |Cite
|
Sign up to set email alerts
|

SHG in a centrosymmetric crystal – can it be possible?

Abstract: The present report lists selected publications on centrosymmetric compounds that manifest second harmonic generation responses in a laser, along with a few publications that dispute the laser outcomes. Two studies provide a plausible explanation for this apparent contradiction between second-order nonlinear susceptibility and inversion symmetry: the crystals are noncentrosymmetric and are twinned by inversion. If crystal structures of SHG-active compounds are presented in centrosymmetric settings, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…It should be noted that intense second harmonic generation in centrosymmetric crystals is known and typically associated with structural defects as vacancies, distortion of the structure, 79–82 or twins. 83 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that intense second harmonic generation in centrosymmetric crystals is known and typically associated with structural defects as vacancies, distortion of the structure, 79–82 or twins. 83 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…69,77,78 The quenching in Na 3 Gd 1−x Sm x (BO 3 ) 2 is due to the non-radiative energy transfer from excited Sm 3+ ion to non-excited Sm 3+ ions or opening of cross-relaxation channels. 69,77,78 Second harmonic generation It should be noted that intense second harmonic generation in centrosymmetric crystals is known and typically associated with structural defects as vacancies, distortion of the structure, [79][80][81][82] or twins. 83 Fig.…”
Section: Crystengcomm Papermentioning
confidence: 99%
“…A recent study revealed that centrosymmetric crystals can generate the Second Harmonic, in the presence of twinning by inversion or local asymmetry. 52 The components of hyperpolarizability and the second order susceptibility matrix have been calculated for HgBrI ( 1 ) and [Hg(bpy)BrI] ( 2 ), according to Kleinman's symmetry. The assumptions for Kleinman's symmetry are always valid for SHG.…”
Section: Resultsmentioning
confidence: 99%
“…Also difficult to understand is the increasing number of publications that describe the observation of second harmonic generation (SHG) responses upon irradiation with a laser for materials with a centrosymmetric crystal structure, [213] although it has already been shown that a centrosymmetric structure cannot exhibit such properties. [214,215] Measurement of SHG responses even became an experimental tool to prove the absence of centrosymmetry.…”
Section: Space Group Modelsmentioning
confidence: 99%